Impact of era of diagnosis on cause‐specific late mortality among 77 423 five‐year European survivors of childhood and adolescent cancer: The PanCareSurFup consortium. Issue 3 (21st October 2021) - Byrne, Julianne; Schmidtmann, Irene; Rashid, Humayra; Hagberg, Oskar; Bagnasco, Francesca; Bardi, Edit; De Vathaire, Florent; Essiaf, Samira; Winther, Jeanette Falck; Frey, Eva; Gudmundsdottir, Thorgerdur; Haupt, Riccardo; et al.
Abstract: Late mortality of European 5‐year survivors of childhood or adolescent cancer has dropped over the last 60 years, but excess mortality persists. There is little information concerning secular trends in cause‐specific mortality among older European survivors. PanCareSurFup pooled data from 12 cancer registries and clinics in 11 European countries from 77 423 five‐year survivors of cancer diagnosed before age 21 between 1940 and 2008 followed for an average age of 21 years and a total of 1.27 million person‐years to determine their risk of death using cumulative mortality, standardized mortality ratios (SMR), absolute excess risks (AER), and multivariable proportional hazards regression analyses. At the end of follow‐up 9166 survivors (11.8%) had died compared to 927 expected (SMR 9.89, 95% confidence interval [95% CI] 9.69‐10.09), AER 6.47 per 1000 person‐years, (95% CI 6.32‐6.62). At 60 to 68 years of attained age all‐cause mortality was still higher than expected (SMR = 2.41, 95% CI 1.90‐3.02). Overall cumulative mortality at 25 years from diagnosis dropped from 18.4% (95% CI 16.5‐20.4) to 7.3% (95% CI 6.7‐8.0) over the observation period. Compared to the diagnosis period 1960 to 1969, the mortality hazard ratio declined for first neoplasms ( P for trend <.0001) and for infections ( P  < .0001); declines in relative mortality from second neoplasms and cardiovascular causes were less pronounced ( P  = .1105 and P  = .0829, respectively). PanCareSurFup is the largest study with the longest follow‐up of late mortality among European childhood and adolescent cancer 5‐year survivors, and documents significant mortality declines among European survivors into modern eras. However, continuing excess mortality highlights survivors' long‐term care needs. Abstract : What's new? Children and adolescents who survive cancer have increased mortality rates compared with the general population. Here, the authors investigated trends in mortality among European cancer survivors 5 or more years after diagnosis. They pooled data on more than 77 000 patients from 12 cancer registries and clinics across Europe. Patients were diagnosed between 1940 and 2018, and all‐cause mortality fell steeply during this period. However, excess mortality remained high, even for subjects in their 60s, highlighting the need for long term care for childhood cancer survivors.